Antitumor Activity against Human Colorectal Adenocarcinoma of Silver Nanoparticles: Influence of [Ag]/[PVP] Ratio - Omar Ulises Cruz-Ramírez; Lucía Margarita Valenzuela-Salas; Alberto Blanco-Salazar; José Antonio Rodríguez-Arenas; Paris A. Mier-Maldonado; Juan Carlos García-Ramos; Nina Bogdanchikova; Alexey Pestryakov; Yanis Toledano-Magaña (MDPI AG, 2021)
Silver nanoparticles (AgNPs) not only have shown remarkable results as antimicrobial and antiviral agents but also as antitumor agents. This work reports the complete characterization of five polyvinylpyrrolidone-coated AgNP (PVP-AgNP) formulations, their cytotoxic activity against human colon tumor cells (HCT-15), their cytotoxic effect on primary mouse cultures, and their lethal dose on BALB/c mice. The evaluated AgNP formulations have a composition within the ranges Ag: 1.14-1.32% w/w, PVP: 19.6-24.5% and H2O: 74.2-79.2% with predominant spherical shape within an average size range of 16-30 nm according to transmission electron microscopy (TEM). All formulations assessed increase mitochondrial ROS concentration and induce apoptosis as the leading death pathway on HCT-15 cells. Except for AgNP1, the growth inhibition potency of AgNP formulations of human colon tumor cancer cells (HCT-15) is 34.5 times higher than carboplatin, one of the first-line chemotherapy agents. Nevertheless, 5-10% of necrotic events, even at the lower concentration evaluated, were observed. The cytotoxic selectivity was confirmed by evaluating the cytotoxic effect on aorta, spleen, heart, liver, and kidney primary cultures from BALB/c mice. Despite the cytotoxic effects observed in vitro, the lethal dose and histopathological analysis showed the low toxicity of these formulations (all of them on Category 4 of the Globally Harmonized System of Classification and Labelling of Chemicals) and minor damage observed on analyzed organs. The results provide an additional example of the rational design of safety nanomaterials with antitumor potency and urge further experiments to complete the preclinical studies for these AgNP formulations.